Exploring the potential use of pristine and metal-encapsulated B36N36 fullerenes in delivery of β-lapachone anticancer drug: DFT approach. (1st March 2023) - Gholami, Aref; Shakerzadeh, Ehsan; Chigo Anota, Ernesto
Graphical abstract: A systematic density functional theory (DFT) calculations are carried out to examine the potential application of synthesized B36 N36 nanocluster for the design of β-lapachone anticancer drug carriers. Results can provide meaningful data for further experimental studies in the field of nanomedicine domain. Abstract: Motivated by earlier experimental and theoretical studies on the potential of different nanostructures for drug delivery, the application of B36 N36 fullerene is explored as a drug delivery system for anti-cancer β-Lapachone drug based on the dispersion-corrected density functional theory calculations. Results indicate that this fullerene can carry up to six drugs with binding energy per β-Lap of −7.8 kcal/mol in water phase. Furthermore, the influence of alkali or alkaline earth metals (AAM) encapsulation inside the B36 N36 fullerene on the β-Lap adsorption performance is studied. The binding energies per β-Lap for AAM-B36 N36 endohedral fullerenes are found to be larger than pristine B36 N36 in gas and water phases. Therefore, the AAM encapsulation inside the fullerene enhance the adsorption performance of fullerene toward β-Lap adsorption. The desorption mechanisms are examined through p H-dependent and photochemical mechanism of light-triggered. Results indicate that the drug release could be simply occurred in the cancer cells upon protonation is plausible, especially for B36 N36 and K-encapsulated B36 N36 carries. Obtained data might be helpful for development of boron nitride-based nanocarriers in nanomedicine domain.